Journalism: As Seen in the Eyes of Current Journalism and Digital Media Students - Aladdine, Rana (Žurnalistikos tyrimai, 2023)
The world of journalism is complex, multifaceted, and intricate. No consensus exists on the definition of journalism or its characteristics, skill set, and career choices. Differing perceptions stem from journalism’s shifts to new forms, practices, and ways of thought. The digital revolution has drastically transformed the understanding and definition of journalism. Journalists, journalism educators, and even social critics have all offered varying notions on the field. However, the students, a key element, are often neglected in this equation. This paper explores how students view journalism. The current generation is arguably highly equipped with digital media through regular practice, consumption, and exposure to digitization. Journalists-to-be are considered to be the future shareholders and may be the directors of the profession. The study focused on how journalism and digital media students specifically classified journalism characteristics, the educational background they found necessary for journalists, as well as their work aspirations. As journalism is evolving and, in particular, digital journalism is a key factor in the study, the student sample was limited to those registered in the Journalism and Digital Media department at Al Maaref University. Al Maaref University has been categorized as one of the first universities in Lebanon to include the term “digital media” in their journalism degree in hopes of reflecting the fast-changing industry. This study used a quantitative approach based on a survey questionnaire administered online to all students enrolled in the above-mentioned department. Findings showed that the majority of students considered the top characteristics of a journalist to include traditional journalism skills before any digital journalism skills. Students also expressed areas of study at times consistent with those skills and other times consistent with their career choices. Moreover, a majority of current journalism students aspire to work in front of the camera.